Hydrochemical Evaluation of Groundwater from Selected Wells in Al Muthana Governorate, Southern Iraq - Al- Khafaji, Raad; Muhi, Saad; Jassam, Adnan (Iraqi Journal of Science, 2021)
The study area is part of the city of Samawa in Al Muthanna Governorate in southern Iraq. The study area is located to the west of Samawa city bounded by the north latitudes 31⁰11’-31o42’ and east longitudes 44o58’- 45⁰16’and its groundwater resources are developed for supply and irrigation purposes. In order to evaluate the quality of groundwater in the study area, twenty three groundwater samples were collected and analyzed for physical and chemical parameters. Hydrochemical analysis showed that the groundwater of the study area is excessively mineralized and very hard. The increase in flow length of groundwater in the study area caused a change in water quality from bicarbonate to sulfate and chloride. The abundance of the major ions is as follows: SO4> CL>HCO3>NO3and Na>Ca>Mg>K. The dominant type of groundwater is Na+- sulfate. The water of the studied wells is not suitable for human drinking. Depending on TDS and EC values, most samples of the water are moderate saline class for irrigation. Most wells are good to permissible (wells No.4,14,17) and doubtful (well No. 12) for irrigation depending on Na%, while unsuitable for irrigation depending on EC (except well No. 17 which is permissible). Excellent water class (S1)for agriculture was recorded depending on SAR, except for well N0.2 which had an a good class (S2).